2017
DOI: 10.1175/jamc-d-16-0115.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Observation on the Sampling Characteristics of TRMM PR Precipitation

Abstract: Observations of the Tropical Rainfall Measuring Mission Precipitation Radar (TRMM PR) over 16 yr yielded hundreds of large precipitation systems (≥100 km) for each 0.1° grid over major rainy regions. More than 90% of the rainfall was attributed to large systems over certain midlatitude regions such as La Plata basin and the East China Sea. The accumulation of high-impact snapshots reduced the significant spatial fluctuation of the rain fraction arising from large systems and allowed the obtaining of sharp imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Finally, one limitation of this study is that we used only the two and a half years of data from the GPM Ku radar. To obtain the regional characteristics more clearly, the long-term mean at high resolution is necessary, as shown by Hirose et al (2008;2017a;2017b) for precipitation climatologies generated from the TRMM PR. Another limitation is that we examine only those profiles where a bright band is detected and that are classified as stratiform, excluding stratiform precipitation profiles without a bright band under cold environments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one limitation of this study is that we used only the two and a half years of data from the GPM Ku radar. To obtain the regional characteristics more clearly, the long-term mean at high resolution is necessary, as shown by Hirose et al (2008;2017a;2017b) for precipitation climatologies generated from the TRMM PR. Another limitation is that we examine only those profiles where a bright band is detected and that are classified as stratiform, excluding stratiform precipitation profiles without a bright band under cold environments.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the locations of extreme events determined in this study. Note that the numbers of extreme events have latitudinal dependence due to the orbital characteristics of TRMM PR, where the number of PR footprints has a sharp peak at around 348N and 348S (Hirose et al 2017, their Fig. 1).…”
Section: Precipitation Characteristics Of the Extreme Eventsmentioning
confidence: 99%
“…Unlike other sensors, the Precipitation Radar (PR) on the Tropical Rainfall Measuring Mission (TRMM) satellite directly observed precipitation echoes in various regions over a period of more than 16 yr (Hirose et al 2017b). The long-term operation of the PR was realized using an orbit boost, maintaining the orbital altitude using fuel intended for a controlled reentry, and switching between primary and redundant systems (NASA 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have utilized a 0.18 grid spacing to ensure sampling sufficiency. Hirose et al (2017b) demonstrated that TRMM PR has advantages in the detection of orographic and coastal rainfall at the 0.18 scale. Even though these footprintscale gridded data provide the highest-resolution rainfall information of global estimates, comparative studies with regional observations highlight the need for even finerscale datasets to better understand local phenomena and improve the nonuniformity of the data (e.g., Zhang et al 2004;Kirstetter et al 2013;Heymsfield et al 2000).…”
Section: Introductionmentioning
confidence: 99%